Metro News Journalists Critique Food Biotechnology - Tom A. Vestal; Gary E. Briers (Journal of Applied Communications, 1999)
The results of this study may encourage researchers, educators, and industry professionals to change behavior and to collaborate with journalists and the social institution of mass media to inform consumers about food biotechnology. Eighty-eight journalists for 65 of the nation’s largest newspapers provided data for the study. Major findings were as follows: journalists’ knowledge of food biotechnology was relatively low; most journalists considered genetic modification of plants as “acceptable,” and journalists had greatest faith in “university scientists” as sources. Too, “Writers” rather than “Editors” had greater acceptance of genetically modified organisms, greater faith in sources, and less fear of using biotechnology to produce food.